Women's Language Features that Used by Characters in Movie "Tinkerbell: Secret of The Wings" - Temaja, Aswinda Eka (Udayana Journal of Social Sciences and Humanities, 2024)
This study entitled Women’s Language Features that Used by Character’s in Movie: “Tinkerbell: Secret of the Wings”. The aims to identifying of women’s language features and find out the function of the language in the movie based on theory applied. The data of this study was taken from observation and taking note the dialogue of characters on the movie using documentation method and the method applied was documentation method. The collected data were selected and put into categories of women’s language features and categorized their function which were descriptively analysed based on the theory applied. The result showed that 9 features and 5 function founded in the movie .